Analisis Kompetensi Individu Terhadap Kinerja Karyawan di PT. Semen Indonesia Logistik (SILOG) - Tantria Desvi Vinata Sari; Cindy Silvia Agustin; M. Isa Anshori (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2024)
Individual Competency describes a characteristic or ability possessed by each employee in carrying out work. Of course, paying attention to existing factors and indicators can create quality competencies and improve employee performance. By using the literature study method, it is hoped that we will be able to analyze individual competencies accurately according to data from existing sources. So in this case, the development of human resources within the company will be of high quality. This article describes individual competencies which include the relationship between employee performance and motives, traits, self-concept, knowledge and skills, and the benefits for the company and employees. This material is designed to help employees develop their ability to develop, increase resilience, ability to face problems and develop skills in innovation and improve their individual performance. With individual competency, employees can shape their personality and increase employee knowledge, and employee skills will have a positive impact on maximizing company productivity.